Neonatal Diet and Gut Microbiome Development After C-Section During the First Three Months After Birth: A Systematic Review - Pivrncova, Eliska; Kotaskova, Iva; Thon, Vojtech (Frontiers in Nutrition, 2022)
Background: C-section delivery imprints fundamentally on the gut microbiota composition with potential health consequences. With the increasing incidence of C-sections worldwide, there is a need for precise characterization of neonatal gut microbiota to understand how to restore microbial imbalance after C-section. The gut microbiota development after birth is shaped by various factors, importantly it is the infant’s diet and antibiotic exposure. Concerning diet, current research has proposed that breastfeeding can restore the characteristic gut microbiome after C-section. Objectives: In this systematic review, we provide a comprehensive summary of the current literature on the effect of breastfeeding on the gut microbiota after C-section delivery in the first three months of life. Methods: The retrieved data from PubMed, Scopus, and Web of Science were evaluated according to the PICO/PECO strategy. Quality assessment was conducted by Newcastle-Ottawa Scale. PROSPERO registration No. CRD42021287672 Results: After critical selection, we identified 14 studies out of 4628 for the evaluation of the impact of the diet after C-section delivery. The presented results demonstrate consistent evidence that C-section and affiliated intrapartum antibiotic exposure affects Bacteroidetes abundance and the incapacity of breastfeeding to reverse their reduction. Furthermore, there is a positive effect of exclusive breastfeeding on Actinobacteria and Bifidobacteria restoration over the 3 months after birth. None of the included studies detected any significant changes in Lactobacillus abundance in breastfed infants after C-section. Conclusion: C-section and intrapartum antibiotic exposure influence an infant’s gut microbiota by depletion of Bacteroides regardless of the infant’s diet in the first three months of life. Even though breastfeeding increases the presence of Bifidobacteria, further research with proper feeding classification is needed to prove the restoration effect on some taxa in infants after C-section.